THE MARKETING EFFICIENCY FOR THE SOME VEGETABLE CROPS IN THE AGRICULTURAL PROVINCE OF BAGHDAD FOR SEASON SUMMER 2014 - & et al., Al fraji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Vegetables are considered important agricultural commodities for consumer , because they contain proteins carbohydrate, oil, and vitamins. There is an increasing demand for these products which makes the process to reach the consumer in suitable prices a necessary task . Agricultural marketing has an important role in making the price for these products especially the agricultural marketing . the object of this paper is to calculate the marketing margin for some vegetable crops, like tomatoes, cucumber, onions and potatoes, between whole sale price and consumer price in Baghdad province and to calculate the relative importance for marketing margin items. The research arrived to some results like that the marketing margin between wholesale price and consumer price represents an important part of what consumer spends as it was about 35.6% for tomatoes, 39.0% for cucumber, 23.0% for eggplant, and 36.6% for potatoes, 35.8% for onions and as average for all vegetables was about 34.1 % the relative importance of marketing margin components came in the first place , the profits of retailer as it was on average for all vegetables about 42.6% and in the second place was come transportation costs as it relative importance was on average about 18.8% while the relative importance of marketing operations was 17.7%. And then came the marketing operations, packaging and loading costs.